The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fgene.2021.770014
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Identification and Evolution of the PP2C Gene Family in Eight Rosaceae Species and Expression Analysis Under Stress in Pyrus bretschneideri

Abstract: Type 2C protein phosphatase (PP2C) plays an essential role in abscisic acid (ABA) signaling transduction processes. In the current study, we identify 719 putative PP2C genes in eight Rosaceae species, including 118 in Chinese white pear, 110 in European pear, 73 in Japanese apricot, 128 in apple, 74 in peach, 65 in strawberry, 78 in sweet cherry, and 73 in black raspberry. Further, the phylogenetic analysis categorized PbrPP2C genes of Chinese white pear into twelve subgroups based on the phylogenic analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
(99 reference statements)
1
8
0
Order By: Relevance
“…JrVHAG1 was induced by CdCl 2 and further confirmed that its Cd-responsive function is also achieved through the ABA signal pathway [54]. PbrPP2C10, PbrPP2C11, PbrPP2C15, and PbrPP2C18 were up-regulated by exogenous ABA, as a presumption that PbrPP2C is related to ABA [37]. Therefore, based on the performance of JrPP2Cs under different stress and ABA in this study and other previous reports, we believe that the response of walnut PP2C family genes to stress is related to ABA signal.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…JrVHAG1 was induced by CdCl 2 and further confirmed that its Cd-responsive function is also achieved through the ABA signal pathway [54]. PbrPP2C10, PbrPP2C11, PbrPP2C15, and PbrPP2C18 were up-regulated by exogenous ABA, as a presumption that PbrPP2C is related to ABA [37]. Therefore, based on the performance of JrPP2Cs under different stress and ABA in this study and other previous reports, we believe that the response of walnut PP2C family genes to stress is related to ABA signal.…”
Section: Discussionmentioning
confidence: 55%
“…In order to reveal the adversity adaptation mechanism of walnuts then to provide a basis for walnut cultivation and management to ensure the yield and quality, in this study, 41 walnut PP2C genes those may have potential functions in stress response were identified (Table 1). The sequence characteristics (ORF length, amino acid number, molecular weight, and pI) of JrPP2Cs (Table 1) were ranged similarly as other species, for instance, the molecular weights of PP2C proteins from Pyrus bretschneideri, tomoto and current walnut were 7.5 ~ 243 [37], 6.7 ~ 120 [26], and 18.6 ~ 119 kDa, respectively. In terms of evolutionary relationship, the 41 JrPP2C proteins shared a high similarity with the members of PP2C family of Arabidopsis and poplar, and could be classified into eleven subfamilies with reference to the classification in Arabidopsis [38], and wild soybean [39] (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Fifty-six FvPP2C and 228 FaPP2C genes were identified by homology comparison ( Supplementary Tables S1 and S2 ). Obviously, the amount of FvPP2C in woodland strawberry was much less than that in A. thaliana (80) [ 29 ], rice (78) [ 29 ], wheat (95) [ 49 ], apple (128) [ 50 ], and peach (74) [ 50 ], while the amount of FaPP2C in pineapple strawberry was higher. In addition, 56 CsPP2Cs were identified in cucumber, which was consistent with woodland strawberry.…”
Section: Discussionmentioning
confidence: 99%
“…The PP2C gene family members in most plants such as A. thaliana [ 29 ], rice [ 29 ], wheat [ 50 ] and cucumber [ 51 ] were divided into 13 subfamilies by systematic cluster analysis. In this study, the PP2C genes of A. thaliana , woodland, and pineapple strawberries were divided into 11 subfamilies ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PP2C genes encode crucial signaling molecules in developmental processes, phytohormone signaling, and stress responses in Arabidopsis spp., maize, and members of the Rosaceae family (Kerk et al, 2002;Wei and Pan 2014;Guo et al, 2021). However, characterization of the chestnut PP2C gene family was yet to be undertaken, despite the availability of the chestnut genome sequence.…”
Section: Discussionmentioning
confidence: 99%